A cadaveric of the course and characteristics of the greater palatine artery - Koutras, Sandra (My University, 2019)
Background: The purpose of this study was to detail the topography of the greater palatine artery (GPA), looking specifically at its depth from the overlying masticatory mucosa as well as its diameter so as to be able to ascertain the safest area for graft harvesting from partially and fully edentate individuals. Methods and materials: Thirty-six maxillae from human cadavers, whose age and sex are known, were analysed at the School of Anatomical Sciences, University of the Witwatersrand, Johannesburg, South Africa. Following dissection of 72 GPA, the width and length of the palate as well as the diameter of the greater palatine artery and its relationship to the overlying palatal mucosa was recorded at 3mm intervals. Results: A total of 64 GPA were evaluated. Despite a relatively even distribution of male and female individuals, there was no statistically significant difference between the sexes. The left and right diameters of the GPA as well as the right and left distances from the GPF to the palatal raphe were not found to be significantly different. The depth of the GPA decreased as it coursed anteriorly from the greater palatine foramen ranging from 6.67 mm to 4.35 mm. The depth at both the 3mm and 6mm intervals decreased by approximately 1.2mm with an increase of 10mm in palatal width. Conclusion: No directional asymmetry or sex and age bias could be found. Wider palates tend to have shallower GPAs posteriorly at the 3mm and 6mm landmark. A new landmark is recommended for use in partially dentate and edentulous individuals to measure the GPA depth at the point where the palatal raphe bisects a line adjoining the two GPFs.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master in Dentistry Johannesburg, 2019